The Effect of Standardized Guidelines on Nurse’s Knowledge and Practices Regarding Hemodialysis at Tertiary Care Hospital Lahore (Medical Forum Monthly, 2023)
Objective: To assess the effect of standardized guidelines on nurse’s knowledge and practices regarding hemodialysisStudy Design: Quasi-experimental studyPlace and Duration of Study: This study was conducted at the Dialysis Unit of Tertiary Care Unit of Lahore fromMay, 2022 to September, 2022.Materials and Methods: Thirty two nurses who were working in the dialysis unit having at least 6 months of working experience. Nurses who had excellent knowledge regarding patient care or enrolled in any other program were excluded from the study. The knowledge of the participants was assessed through adopted questionnaire and the performance of the participants was evaluated via hemodialysis unit performance checklist.Results: Twenty (62.5%) nurses were between 25-30 years, 9 (28.1%) were between 31-35 years and only 3(9.4%) were between 36-40 years, at baseline, only 3.1% of respondents had some good knowledge of the guidelines while after getting the educational sessions, 90.6% showed excellent knowledge. Furthermore, when the practice was evaluated, it was noted that only 12.5% of nurses were doing safe practices according to the standardized guidelines and after all the sessions, 87.5% of the participants started safe practices.Conclusion: Majority of the nurses had no knowledge and orientation of Standardized Guidelines for hemodialysis patients at the start of the study. After all the educational sessions, the most of the nurses exhibited excellent to good knowledge whereas safe practices for the above mentioned population of patients. There was statistically significant difference among the knowledge and practice scores before and after sessions and a significant effect of standardized guidelines on nurses' knowledge and practice regarding hemodialysis.